CAR T cells or allogeneic transplantation as standard of care for advanced large B-cell lymphoma: an intent-to-treat comparison - Dreger, Peter; Dietrich, Sascha; Schubert, Maria-Luisa; Selberg, Lorenz; Bondong, Andrea; Wegner, Mandy; Stadtherr, Peter; Kimmich, Christoph; Kosely, Florentina; Schmitt, Anita; Pavel, Petra; Liebers, Nora; et al. (Blood advances, 2020)
CD19-directed chimeric antigen receptor (CAR) T-cell treatment has evolved as standard of care (SOC) for multiply relapsed/refractory (R/R) large B-cell lymphoma (LBCL). However, its potential benefit over allogeneic hematopoietic cell transplantation (alloHCT) remains unclear. We compared outcomes with both types of cellular immunotherapy (CI) by intention to treat (ITT). Eligble were all patients with R/R LBCL and institutional tumor board decision recommending SOC CAR T-cell treatment between July 2018 and February 2020, or alloHCT between January 2004 and February 2020. Primary end point was overall survival (OS) from indication. Altogether, 41 and 60 patients for whom CAR T cells and alloHCT were intended, respectively, were included. In both cohorts, virtually all patients had active disease at indication. CI was recommended as part of second-line therapy for 21 alloHCT patients but no CAR T-cell patients. Median OS from indication was 475 days with CAR T cells vs 285 days with alloHCT (P = .88) and 222 days for 39 patients for whom alloHCT beyond second line was recommended (P = .08). Of CAR T-cell and alloHCT patients, 73% and 65%, respectively, proceeded to CI. After CI, 12-month estimates for nonrelapse mortality, relapse incidence, progression-free survival, and OS for CAR T cells vs alloHCT were 3% vs 21% (P = .04), 59% vs 44% (P = .12), 39% vs 33% (P = .97), and 68% vs 54% (P = .32), respectively. In conclusion, CAR T-cell outcomes were not inferior to alloHCT outcomes, whether measured by ITT or from CI administration, supporting strategies preferring CAR T cells over alloHCT as first CI for multiply R/R LBCL.
Gesehen am 10.02.2022